PENINGKATAN HASIL BELAJAR IPS TENTANG JENIS-JENIS PEKERJAAN MELALUI METODE COOPERATIVE LEARNING TIPE INSIDE-OUTSIDE CIRCLE (IOC) DI KELAS III SDN KARET 06 PAGI JAKARTA SELATAN - Sudrajat, Ajat (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
The purpose of this study was to analyze the IPS Improved Learning Outcomes third grade students of SDN Karet 06 Pagi South Jakarta on material Types of Work Method Using Cooperative Learning Type Inside-Outside Circle. Research conducted at SDN Karet 06 Pagi South Jakarta, a study was conducted for three months from March to May 2015 samapai in the second semester of the school year 2014-2015. The study was conducted using the method of classroom action research (PTK). The research was conducted in two siklus. Result of the Â research indicates data obtained by IPS data from the learning process by using Cooperative Learning Type Inside-Outside Circle. At IPS cognitive learning outcomes gained 60% increase to 86.67% in the second cycle. Affective aspects of learning outcomes IPS consisting of Discipline 70%, communicative 81%, responsibility 67% increase to 87% Discipline, communicative 87%, responsibility 80% in the second cycle. Psychomotor aspects of learning outcomes first cycle that preparation indicator 67% increase in the second cycle to 84% 68% Process indicators increased in the second cycle to 79%, and the indicator of the results of a 77% increase in the second cycle to 81% .Prosentase teacher activity in the first cycle 67% and cycle II reached 93%. The percentage of student activity first cycle of 60% and cycle II reached 90% .Implikasi of this research is the IOC Cooperative Learning mode can be used as one of learning methods to improve learning outcomes IPS elementary school third grade students.